ANALYSING THE INFLUENCE OF CREATIVITY AND INNOVATION EMPLOYEE ON DEVELOPMENT OF MAQNA HOTEL GORONTALO - Kezia, Panambunan Eunike Monicca; Pangemanan, Sifrid S.; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Within the company in order to be able to compete with other companies it is necessary to carry out creativity and innovation continuously. With the creativity that creates new ideas or ideas that are able to produce new products that have not been previously available and can be used by companies. innovation that gives more values to a product with a new idea that is different from other products. This study aims to determine the effect of creativity and innovation employee of Â Maqna Hotel Gorontalo. The population is 150 employees and the sample is 60 respondents and researchers use slovinâ€™s formula. The analytical method using multiple regression analysis. The result of this study indicate that simultaneously creativity and innovation on development of Maqna Hotel Gorontalo. It is better for Maqna Hotel Gorontalo employee to improve and development the creativity and innovation that is owned for the development of Maqna Hotel Gorontalo.Keywords: creativity, innovation, development companyÂ